Does environmental policy stringency foster innovation and productivity in OECD countries? - Rafael Morales-Lage; Aurelia Bengochea-Morancho; Inmaculada Martínez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
In this paper we use panel data models and quantile regressions to test the "weak" and "strong" versions of the Porter hypothesis, using data from 14 OECD countries over the period 1990-2011. A newly-released environmental policy stringency index (EPS) provided by the OECD is used as an indicator of the stringency of environmental regulations in order to tackle endogeneity issues of proxies used in earlier research. The findings indicate that more stringent environmental regulations positively influence R&D expenditure, the number of patent applications and total factor productivity (TFP). The results show that environmental stringency has a positive effect on R&D, mainly for the lower quantiles (0.10, 0.25) of the distribution of R&D, whereas for the number of patent applications and total factor productivity, the effect increases for the highest quantiles (0.75, 0.90) of the distribution of the targeted indicators.
Keywords: Q43; Q48; Q53; 330; environmental regulations; Porter hypothesis; OECD; innovation; quantile regression